2020
DOI: 10.1177/1533033820980116
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Vessel Normalization: A Window to Enhancing Cancer Immunotherapy

Abstract: Hostile microenvironment produced by abnormal blood vessels, which is characterized by hypoxia, low pH value and increasing interstitial fluid pressure, would facilitate tumor progression, metastasis, immunosuppression and anticancer treatments resistance. These abnormalities are the result of the imbalance of pro-angiogenic and anti-angiogenic factors (such as VEGF and angiopoietin 2, ANG2). Prudent use of anti-angiogenesis drugs would normalize these aberrant tumor vessels, resulting in a transient window of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 147 publications
0
25
0
Order By: Relevance
“…In humans, EGFR/ErbB (the epidermal growth factor receptors), RTKs (group of receptor tyrosine kinases) comprised, ErbB2/Neu/ HER-2, EGFR/ErbB1/HER-2 & ErbB3/HER-3 [49,50]. ERBB2 is deficient in ligand binding capabilities due to its stable but enlarged ectodomain, nonetheless, it is chosen for heterodimerization on EGFR to extend the period and strength of the signals induced by the creation of high-affinity complexes with EGFR.…”
Section: Receptor Tyrosine Kinases In the Egfr/erbb Familymentioning
confidence: 99%
“…In humans, EGFR/ErbB (the epidermal growth factor receptors), RTKs (group of receptor tyrosine kinases) comprised, ErbB2/Neu/ HER-2, EGFR/ErbB1/HER-2 & ErbB3/HER-3 [49,50]. ERBB2 is deficient in ligand binding capabilities due to its stable but enlarged ectodomain, nonetheless, it is chosen for heterodimerization on EGFR to extend the period and strength of the signals induced by the creation of high-affinity complexes with EGFR.…”
Section: Receptor Tyrosine Kinases In the Egfr/erbb Familymentioning
confidence: 99%
“… 106 Over the past decade, compelling research has shown that the judicious use of anti-angiogenic therapies can temporarily normalize tumor vasculature and increase drug and anti-tumor immune cell delivery while alleviating hypoxia in the TME, thereby increasing the effectiveness of various treatments. 107 Tumor vascular normalization has been shown to improve the efficacy of cancer immunotherapy, and recent studies have shown that enhanced immune stimulation can in turn improve tumor vascular normalization. 108 Interferon γ is produced by activated T cells and induces T-cell migration; it plays an important role in this process.…”
Section: Biological Rationale For the Anti-angiogenic-immunotherapy C...mentioning
confidence: 99%
“…Feedback between ICB and anti-angiogenic enhances itself and ultimately drives immune-mediated tumor cell eradication. 107 …”
Section: Biological Rationale For the Anti-angiogenic-immunotherapy C...mentioning
confidence: 99%
See 1 more Smart Citation
“…New angiogenesis actually plays a key role in tumor development, invasion, and metastases formation of many cancers, including NMSC [ 18 , 19 ]. Vascular Endothelial Growth Factor (VEGF) family is considered to be a fundamental key factor involved in angiogenesis, influencing progression, prognosis and therapy in various forms of cancers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Specific variations of VEGF genes have been demonstrated to be genetic determinants for susceptibility, outcome and therapy response, especially for the solid tumors.…”
Section: Introductionmentioning
confidence: 99%